ANALISIS PENGARUH STRATEGI PEMERINTAH KABUPATEN PEKALONGAN DAN PARTISIPASI KELOMPOK SADAR WISATA TERHADAP PENGEMBANGAN EKOWISATA PETUNGKRIYONO - Muhammad Naufal Irfan; Edi Santosa; D Ghulam Manar (Journal of Politic and Government Studies, 2016)
Tourism is one industry that can be relied upon to benefit the government and the people living in the area concerned. For the government as a provider and manager of tourism, the tourism sector will stimulate the economy of the region, driving the pace of regional development, and improve the welfare of the people in the regions concerned. This research was conducted with aim to identify various strategies of government of Pekalongan regency in developing Ecotourism Petungkriyono, by analyzing participation of tourism awareness groups in developing Ecotourism Petungkriyono, and determine relationship between the Government of Pekalongan District with the groups of tourism awareness in the development of Ecotourism Petungkriyono. The method used in this study was a mixed methods, a method that combines qualitative and quantitative approaches in terms of methodology combines two approaches in all stages of the research process. The population and sample in this research are the community of Petungkriyono District which affiliate into the manager of tourism awareness groups, through questionnaires and interviews supported with an explanation. This study used the population study, because the population is less than 100 respondents, as many as 84 respondents who are the managers of 3 tourism awareness groups, and 11 informants. These results indicate that strategy of the Government of Pekalongan District and tourism awareness groups participation effect on the development of the potential of Ecotourism Petungkriyono. There are no specific regulations provided to organize the development of Ecotourism Petungkriyono, lack of access roads, and the lack of coordination among stakeholder institutions which become main constraints on development efforts. Recommends the government to promote the development of Ecotourism Petungkriyono with optimal coordination between the stakeholders involved, and the need for specific policies drafted to Ecotourism Petungkriyono development. In addition, the community needs to increase the number of groups of tourism awareness and strengthen the institution. Keywords: Strategy, Participation, Tourism Awareness Group, Ecotourism, Petungkriyono